Basic electronics for engineers - Lueg, Russell E. (International Textbook Co, 1963)
Contents: Symbols, physical constants; Basic Concepts; The Diode; Electronic circuit- analysic techniques; The Transistor; The Transistor used as a linear device; The vacuum tube.